The Input-Output Approach in Semiclassical Electrodynamics of Keller-Segel Equation - Nieto-Chaupis, Huber (2020)
When the Keller-Segel equation is treated in a semiclassical scenario of electrodynamics involving Quantum Mechanics measurements, it is possible to implement the formalism of input-output in a nature manner without ambiguities. In this paper we explore such edge of this mathematical-biology equation in a systematic manner to describe virus and bacteria colonization in a healthy host. We provide numerical calculations in terms of energy. Present a set of diagrams that might enclose information about the realization of bacterial aggregations in their purpose to carry out a specific task. For this end we implement the concept of transfer function of a system. Simulations are presented in order to make predictions and validate the ideas of the proposal of this paper.